2021
DOI: 10.3389/fimmu.2021.742941
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinflammatory Immune Response and COVID-19: A Double Edged Sword

Abstract: The coronavirus disease-19 (COVID-19) elicited by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused devastating health, economic and social impact worldwide. Its clinical spectrum ranges from asymptomatic to respiratory failure and multi-organ failure or death. The pathogenesis of SARS-CoV-2 infection is attributed to a complex interplay between virus and host immune response. It involves activation of multiple inflammatory pathways leading to hyperinflammation and cytokine storm, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 121 publications
(185 reference statements)
2
84
0
Order By: Relevance
“…IL-1, IL-6, TNF-α, and TGF-β are important pro-inflammatory cytokines that contribute to the pathophysiology of the cytokine release syndrome (CRS), ARDS and multi-organ failure in critically sick adult COVID-19 patients with viral sepsis [13][14][15][16][17][18][19][20][21][22][23] as well as children and adolescents with COVID-19 who develop a multi-system inflammatory syndrome (MIS-C) [59][60][61][62]. Recently, we demonstrated that RJX prevents in the LPS-GalN mouse model of sepsis the marked increase of each of these cytokines in the serum as well as lungs and liver [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-1, IL-6, TNF-α, and TGF-β are important pro-inflammatory cytokines that contribute to the pathophysiology of the cytokine release syndrome (CRS), ARDS and multi-organ failure in critically sick adult COVID-19 patients with viral sepsis [13][14][15][16][17][18][19][20][21][22][23] as well as children and adolescents with COVID-19 who develop a multi-system inflammatory syndrome (MIS-C) [59][60][61][62]. Recently, we demonstrated that RJX prevents in the LPS-GalN mouse model of sepsis the marked increase of each of these cytokines in the serum as well as lungs and liver [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several monoclonal antibodies that serve as inhibitors of the receptors and/or signaling pathways activated by specific pro-inflammatory cytokines are being developed and evaluated as anti-inflammatory drug candidates for prevention of CRS-related complications of severe COVID-19, including but not limited to the IL-1 receptor antagonist Anakinra (Kineret), IL-6 receptor antagonist tocilizumab (Actemra), TNF-α inhibitor infliximab (Remicade) [14,15,22,42,[49][50][51][52]. A major potential advantage of RJX versus biotherapeutic agents such as monoclonal antibodies that inhibit specific cytokine pathways is its ability to inhibit multiple pathways combined with its low cost of production which should make it readily available in low-to middle-income countries and therefore its further development and assessment as a potential COVID-19 drug candidate has potential global relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] These factors might be linked to a hyperinflammatory syndrome, which favors an exaggerated immune response and organ failure when facing a viral infection. [8,9] Some ecological studies have evaluated COVID-19 mortality in high-altitude places, but the results are contradictory. Some authors reported higher mortality in men younger than 65 years old living in the USA and Mexico at >2,000 m elevation than in those located <1,500 m. [10] Other studies developed in an Andean population (Colombia and Perú) showed a negative correlation between high altitude and COVID-19 mortality and lower mortality excess.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the inflammatory responses incurred by SARS-CoV-2 involve diversified upstream stimuli, multiple signaling pathways, and numerous downstream effectors. 3 Therefore, targeting any particular cytokine or even signaling pathway may not be sufficient in alleviating the systemic overreaction of immune system in severe COVID-19, namely cytokine storm. It is urgent and pivotal to develop means which can systemically tuning down the exaggerated immune responses via a relative central node in the inflammation signaling cascades.…”
mentioning
confidence: 99%